Control of postharvest diseases in longan fruit by ozone - K. Whangchai (2018)
In order to study the effects of ozone gas treatment on postharvest diseases of longan fruits, cultures of the fungi Lasiodiplodia sp. and Cladosporium sp. cultured on potato dextrose agar (PDA) were exposed to 20 ppm of ozone. The ozone was applied directly on mycelia of Lasiodiplodia sp. or spore suspension of Cladosporium sp. for 15, 30, 60 and 120 minutes. In vitro studies showed that ozone exposure for 60 minutes significantly reduced mycelial growth of Lasiodiplodia sp. and completely inhibited Cladosporium sp. After fumigation with ozone, microscopic observation revealed the presence of abnormal mycelia of Lasiodiplodia sp. Exposing fruits to ozone for 60 minutes soon after inoculation with Lasiodiplodia sp. and Cladosporium sp. was the most effective way of controlling the incidence of postharvest diseases. Therefore, application of ozone could be considered as a possible alternative method to control postharvest decay and prolong storage life of longan fruits.